Achyranthes aquatica Br.-a New Record for the Flora of Upper Gangetic Plain - Singh, O. P.; Singh, S. K. (Indian Forester, 1982)
The present note deals with Achyrant hes aquatica Br.- a new record for the Flora of Upper Gangetic Plain, from Minag and Gujar Tal of Shahganj Tehsil of District Jaunpur, U.P. Information regarding its distribution, observation in the field, phytogeography, phenology, occurrence and field number have been presented.